INOVASI PELAYANAN KESEHATAN GANCANG ARON DI KABUPATEN BANYUWANGI DALAM PERSPEKTIF MATRIK INOVASI SEKTOR PUBLIK - Anugerah Yuka Asmara; Amy Yayuk Sri Rahayu (Department of Public Administration, Universitas Negeri Surabaya, 2019)
Public sector innovation has been an enticing discourse and practice implemented by governmental agencies in Indonesia. One of popular types of public sector innovation is public service innovation because it directly effects to public as users. Also, it makes positive climate to emerge many innovation forms of public services in Indonesia, particularly on health public service which is widely paid attention by many scholars, practicians, governmental actors, and public as users. In the Blambangan Public Hospital (RSUD-Blambangan) in Banyuwangi Regency, The Gancang Aron innovation is emerged as solution to reduce long queue for patients and their familes in taking medicine in this hospital. This innovation is appreciated as Top 40 of The Best Public Sector Innovation in Indonesia held by Ministry of Administrative and Bureaucratic Reform - Republic of Indonesia. Surely, public service innovation is not singly occurred without absence of any changes at an organization management level. This study focuses on The Gancang Aron innovation at The RSUD-Blambangan in Banyuwangi Regency. This study is a qualitative-descriptive by combining literatures review of public sector innovation and reinforced by field data result. The research finding is that innovation occuring in RSUD-Blambangan is integral part of public service innovation that it can be viewed through public sector innovation matrix.